Production of Briquetted Semicoke from Wood Waste by Multistep Low-Temperature Pyrolysis; Coke and Chemistry; Vol. 63, iss. 12 - Larionov K. B. Kirill Borisovich; Yankovsky S. A. Stanislav Aleksandrovich; Gubin V. E. Vladimir Evgenievich; Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich; Ulko A. A. Aleksandr Anatoljevich; Gasparian G. D. (2020, 2020)
Title screen